The Influence of Empowerment and Job Satisfaction on the Organizational Citizenship Behavior of Elementary School Teachers - Triningsih Triningsih; Sri Setyaningsih; Herfina Herfina (Peneliti.net, 2023)
The purpose of this study was to analyze the influence of empowerment and job satisfaction on Organizational Citizenship Behavior (OCB) among elementary school teachers. The research utilized a quantitative method with a survey approach. The sample consisted of 302 certified and accredited primary school teachers, selected through simple random sampling technique. The statistical tests employed in this study included descriptive analysis, hypothesis testing using path analysis, correlation analysis, and determination coefficient analysis. The research findings revealed the following results: (1) there is a direct positive effect of empowerment on Organizational Citizenship Behavior (OCB) with a path coefficient of 0.455, indicating that the development of empowerment can strengthen OCB; (2) there is a direct positive effect of job satisfaction on Organizational Citizenship Behavior (OCB) with a path coefficient of 0.127, indicating that increasing job satisfaction can strengthen OCB; (3) there is an indirect effect of empowerment on Organizational Citizenship Behavior (OCB) through job satisfaction with a path coefficient of 0.356, suggesting that the development of empowerment can strengthen OCB through the enhancement of job satisfaction. In conclusion, this study emphasizes the importance of considering empowerment and job satisfaction to enhance Organizational Citizenship Behavior (OCB) among elementary school teachers.